The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1111/hepr.12726
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hepatitis B surface antigen seroclearance‐related immune factors

Abstract: The ultimate aims of the treatment of hepatitis B virus infection are the loss of hepatitis B surface antigen (HBsAg) and hepatitis B surface antibody seroconversion. Unfortunately, these goals are rarely reached. Many factors are associated with HBsAg seroconversion, including genetic, immune, and viral factors. However, the mechanism of HBsAg seroclearance, and particularly the immune mechanism, is still difficult to elucidate. The immune factor interferon-α is currently the main antiviral therapy for chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 104 publications
0
15
0
Order By: Relevance
“…HBsAg seroclearance is mainly viewed as the consequence of complex and appropriate immune responses during the course of infection. 31 NA-based therapy does not have substantial immunomodulatory effects compared to other treatment options, such as pegylated interferon. 32 Regardless, higher rates of HBsAg seroclearance are often observed during HBeAg-positive phases of HBV when patients are undergoing treatment with any antiviral agent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HBsAg seroclearance is mainly viewed as the consequence of complex and appropriate immune responses during the course of infection. 31 NA-based therapy does not have substantial immunomodulatory effects compared to other treatment options, such as pegylated interferon. 32 Regardless, higher rates of HBsAg seroclearance are often observed during HBeAg-positive phases of HBV when patients are undergoing treatment with any antiviral agent.…”
Section: Discussionmentioning
confidence: 99%
“…We defined the "baseline" visit at ART-initiation and "follow-up" visits at each yearly visit thereafter until the date A1762T/G1764A mutations (P < .001). Patients were followed for a median 36 months (IQR = [24][25][26][27][28][29][30][31][32][33][34][35][36]. Cumulative proportion of undetectable HBV-DNA was significantly higher in patients with baseline mutation (pcG1896A = 86.6% vs no pcG1896A = 66.9%, P = .04), but not after adjusting for baseline HBV-DNA levels and anti-HBV agent (P = .2).…”
Section: Study Design and Visitsmentioning
confidence: 99%
“…The exact mechanism of HBsAg seroclearance is still unclear, and there is no targeted treatment to achieve this endpoint . However, the evaluation of NA treatment withdrawal in patients with HBeAg‐negative hepatitis B studies has shown higher HBsAg loss rates than in studies with long‐term NA or combined NA and pegylated interferon alfa.…”
Section: Resultsmentioning
confidence: 99%
“…The function of regulatory T cells is reduced in patients given NA therapy owing to a decrease in the helper T cell‐mediated ability of B cells to produce antibodies. In untreated patients, HBV is reduced by elimination of HBV‐infected liver cells through natural immunity . In contrast, the main anti‐HBV activity of NA is inhibition of reverse transcriptase .…”
Section: Discussionmentioning
confidence: 99%
“…In untreated patients, HBV is reduced by elimination of HBV-infected liver cells through natural immunity. [41][42][43] In contrast, the main anti-HBV activity of NA is inhibition of reverse transcriptase. 44 Therefore, there may be differences in the amounts of cccDNA at the time of HBsAg seroclearance between cases of natural elimination and cases of elimination by NA therapy, and release of trace amounts of HBsAg may be more likely to occur from the remaining cccDNA.…”
Section: Discussionmentioning
confidence: 99%